Mediterranean diet pattern behaviors and related socio-demographic factors in a sample of nurses: results of an observational study in Italy - Shaholli, David; De Lucia, Francesco; Ferrante, Carolina; Moretti, Luca; Vezza, Francesca; Barletta, Vanessa India; Cocchiara, Rosario Andrea; La Torre, Giuseppe (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Interest in the dietary habits of healthcare professionals, particularly nurses, has increased in recent years. Nurses play a key role in promoting healthy habits among patients, yet often struggle to maintain a balanced diet due to the demanding nature of their profession.Study Design. Cross-sectional.Methods. The sample identified consisted of working students who attend the master’s degree course in “Nursing and Midwifery Sciences” at the University of Rome “La Sapienza” and nurses inscribed in several Italian nurses’ groups on Facebook, like “Infermiere professionista della salute”, “Infermieri attivi”, “Infermieri di Roma e Provincia” and “Infermieri Roma”. A snowball sampling was used. This observational study was carried out from May to September 2020 through an online platform, and explores the dietary habits of 549 nurses, examining correlations between eating behaviors (Mediterranean Diet Score) and work conditions, such as shift patterns, work hours, and contract types.Results. The Mediterranean Diet Score had a mean value of 7.50 (SD = 1.69). Results show that 90.2% of participants can take short breaks (5-10 minutes) for meals, although stress often affects the quality of these breaks. Nurses with permanent contract (β = 0.098; p = 0.021) and part-time schedules (β = 0.106; p = 0.012) reported healthier eating habits and greater adherence to the Mediterranean diet.Conclusions. The findings highlight the need for improved access to healthy food during long shifts and the implementation of nutritional education programs to support healthier eating habits among nurses.